Estrategias publicitarias a través de los medios digitales facebook y twitter para promover la marca smöoy en la ciudad de Guayaquil - Araujo Araujo, María Cecilia (2016)
The present work of investigation, establishes advertising strategies with digital media that can capture customers and increase sales, according to trends and consumer behavior. The theoretical framework refers to the use of social networks as a dynamic interface between individuals, groups and institutions involving sets are identified with the same problems to enhance their resources in areas of product marketing. Social networks like Facebook and Twitter, interact with hundreds of users and potential customers, and build and form new groups and invite members to join social networks…..